Purna Kalasha symbol - Mumbai Archive Project Team (Jio Institute, 2024)
A purna kalasha, a pot filled with mango leaves and coconut, adorns a Koli household. This auspicious symbol serves as a ceremonial offering to the household deity, as well as a decorative motif outside shrines and at the entrances of homes.